Internet of things and artificial intelligence for smart environments - Hoe, Tung Yew (Springer Nature Singapore Pte Ltd., 2024)
In the ever-evolving landscape of technology, Internet of Things (loT) and Artificial Intelligence (AI) stand as a beacon, illumjnating the path toward smarter, more responsive environments. Thjs book, "Internet of Thjngs and Artificial Intelligence for Smart Environments," embarks on a comprehensive journey through twelve chapters, each dedicated to unraveling the intricacies and unveiling the transformative potential of loT and AI in diverse applications.